2018
DOI: 10.3389/fgene.2018.00570
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Study of Allele-Specific Expression in Colorectal Cancer

Abstract: Accumulating evidence from small-scale studies has suggested that allele-specific expression (ASE) plays an important role in tumor initiation and progression. However, little is known about genome-wide ASE in tumors. In this study, we conducted a comprehensive analysis of ASE in individuals with colorectal cancer (CRC) on a genome-wide scale. We identified 5.4 thousand genome-wide ASEs of single nucleotide variations (SNVs) from tumor and normal tissues of 59 individuals with CRC. We observed an increased ASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
(66 reference statements)
1
22
0
Order By: Relevance
“…We further identified that loss of allelic replication was associated with expression down-regulation at three colon cancer-related gene loci that are also monoallelically expressed. Monoallelic expression has also been reported to differ in frequency between grades of brain tumours (Walker et al, 2012) and occur at different genes in colorectal tumours compared to normal tissue (Liu et al, 2018), suggesting that cancer cells can acquire ectopic allele-specific expression during transformation. Together, our results suggest that altered allelic replication, induced by global changes in DNA methylation, may be a mechanism of gene deregulation within cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…We further identified that loss of allelic replication was associated with expression down-regulation at three colon cancer-related gene loci that are also monoallelically expressed. Monoallelic expression has also been reported to differ in frequency between grades of brain tumours (Walker et al, 2012) and occur at different genes in colorectal tumours compared to normal tissue (Liu et al, 2018), suggesting that cancer cells can acquire ectopic allele-specific expression during transformation. Together, our results suggest that altered allelic replication, induced by global changes in DNA methylation, may be a mechanism of gene deregulation within cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ERASE uses all ASEs rather than summarizing information across a gene, thus retaining ASEs generated due to splicing QTLs. Given the growing popularity of ASE analyses [59][60][61][62] and the increased interest in splicing, ERASE's ability to detect enrichment in small ASE datasets and multiple annotations has the potential to add significantly to biological knowledge. This accounts for biases in ASE discovery due to high read depth and exonic structure.…”
Section: Discussionmentioning
confidence: 99%
“…The AEI quantifies the stoichiometric difference in the expression of the two alleles of a genetic locus [ 26 , 27 , 28 ] or two haplotypes of a diploid individual which can be distinguished at heterozygous variation sites [ 29 ]. Compared to gene expression analysis, AEI has the advantage of using two alleles of one gene within individuals and thus better controlling the genetic background and environmental effects, and therefore can sensitively and accurately detect the genetic and epigenetic differences in highly heterocellular samples such as tumors [ 30 , 31 ]. AEI has been applied to detect driver mutations in various human cancers including colorectal and breast cancer [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%